Aplikasi Penentuan Hasil Persilangan Ular Phyton Molurus Bivittatus Berbasis Android - Rian Dwicahya Supriatman (Jurnal Sistem Informasi Galuh, 2023)
Nowadays, the existence of Sanca Bodo snake (phyton molurus bivittatus)is getting the attention by many people. This kind of snake belong to the favourite animal. Many people are interested to this snake not only for hobby but also for business. The snake lovers and breeders have already successes to cultivate this snake in normal cultivation. Then, many snake lovers want to develop their cultivation by crossing the gen morph is one of the result. Morph is a new kind of snake that has different colour and shade from albino. Technology development in smart phone, such as BlackBerry, Android and iPhone gives so many information for the users. Because of that, the researcher is interested to make an application or software to help the snake lovers and breeders of phyton molurus bivittatus to know the result of genetic crosses. The purpose of this research is to build an information system in application mobile for the snake lovers and breeders nedd. Research method used in this research is Rational Unified Process (RUP) and Unified Modeling Language (UML) for the modeling language. The result of this research has been successful to built an application of information system that can give the information about the genetic crosses of phyton molurus bivittatus based on the pretension. Keywords— design information system, data flow diagram, waterfall.